2004
DOI: 10.3758/cabn.4.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalizations of touch to a fake hand

Abstract: Observers can mislocalize a tactile target delivered to an unseen hand if a visible rubber glove is positioned next to a pair of distractor lights that flash in correlation with the tactile target (Pavani, Spence, & Driver, 2000). In the present study, we explored visual, tactile, and postural factors that influence this fake hand effect. Comparison with baseline conditions revealed that the fake hand effect was larger than a general spatial congruity effect but weaker than the effect obtained when tactile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 20 publications
6
55
1
Order By: Relevance
“…Research has shown that when visual and proprioceptive cues regarding posture are put into conflict artificially (by means of the use of mirrors, video feedback, or artificial body parts), vision often dominates in terms of the final percept (e.g., Austen et al, 2004;Botvinick & Cohen, 1998;Maravita, Spence, Clarke, Husain, & Driver, 2000;Maravita, Spence, Sergent, & Driver, 2002;Nielsen, 1963;Tastevin, 1937). However, in all the previous experiments on selective tactile attention, either only proprioceptive cues (e.g., vision was prevented altogether) or combined congruent proprioceptive and visual cues (e.g., vision was allowed, and proprioception and vision provided correlated postural information) have been used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that when visual and proprioceptive cues regarding posture are put into conflict artificially (by means of the use of mirrors, video feedback, or artificial body parts), vision often dominates in terms of the final percept (e.g., Austen et al, 2004;Botvinick & Cohen, 1998;Maravita, Spence, Clarke, Husain, & Driver, 2000;Maravita, Spence, Sergent, & Driver, 2002;Nielsen, 1963;Tastevin, 1937). However, in all the previous experiments on selective tactile attention, either only proprioceptive cues (e.g., vision was prevented altogether) or combined congruent proprioceptive and visual cues (e.g., vision was allowed, and proprioception and vision provided correlated postural information) have been used.…”
Section: Resultsmentioning
confidence: 99%
“…It will be an interesting question for future research to examine whether a similar pattern of results would be found if the task were altered so that the participants were required to respond on the basis of the somatotopically defined location of the targets instead (i.e., by making one response to targets delivered to the index finger and another response to targets delivered to the thumbs, regardless of the posture adopted-i.e., palm up or palm down; cf. Austen, Soto-Faraco, Enns, & Kingstone, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same visual and tactile stimulation delivered asynchronously has a quite different phenomenology. The rubber hand illusion provides one of the few means of manipulating embodiment, and has been so used in a number of recent studies (Armel & Ramachandran, 2003;Austen, Soto-Faraco, Enns, & Kingstone, 2004;Costantini & Haggard, 2007;Durgin et al, 2007;Ehrsson, Spence, & Passingham, 2004;Ehrsson, Holmes, & Passingham, 2005;Ehrsson et al, 2007;Farnè et al, 2000;Holmes, Snijders, & Spence, 2006;Kanayama, Sato, & Ohira, 2007;Pavani, Spence, & Driver, 2000;Press, Heyes, Haggard, & Eimer, in press;Rorden, Heutink, Greenfield, & Robertson, 1999;Schaefer, Flor, Heinze, & Rotte, 2006;Tsakiris, Prabhu, & Haggard, 2006;Tsakiris, Hesse, Boy, Haggard, & Fink, 2007a;Walton & Spence, 2004).…”
mentioning
confidence: 99%
“…Moreover, by presenting a visual stimulus close to a rubber hand, Farnè et al (2000) demonstrated that cross-modal visual-tactile extinction was stronger when the rubber hand was in a plausible posture relative to the patient's shoulder, as compared to when it was misaligned. Similar eVects of rubber hand posture and orientation have been shown with behavioural studies in healthy individuals (Austen et al 2004;Holmes et al 2006;Pavani et al 2000). These Wndings can be taken as favouring the idea that multisensory inputs processing consists of a weighting of the diVerent senses (e.g., Ernst and Banks 2002;Mon-Williams et al 1997;Ernst and BulthoV 2004), although this is not always the case.…”
Section: Discussionmentioning
confidence: 62%